Meningkatkan Literasi Bahasa Indonesia Melalui Permainan Word Warriors Untuk Anak Migran Indonesia - Anindhea Firdausi Azzahra; Ana Maghfiroh; Niken Reti Indriastuti; Fauzi Alfaidzin (Jurnal Kajian Anak (J-Sanak), 2025)
Literacy development is a fundamental aspect of education, especially in preparing students to face life's challenges. Indonesian immigrant children in Malaysia often have limited literacy skills and are less fluent in Indonesian due to the dominance of the Malay language in daily life. This study aims to identify the impact of a game-based learning approach integrated with daily life on the Indonesian language literacy skills of students at Sanggar Bimbingan Belajar At-Tanzil Pandan Jaya Malaysia. This study uses qualitative methods. Observation and interviews are two data collection methods used by the author in the research. The research was conducted at Sanggar Bimbingan Belajar At-Tanzil Pandan Jaya Malaysia with students aged 9-10 years. This method is used to obtain a comprehensive view of the implementation of the approach. Data were analyzed using interactive qualitative data analysis, which included data reduction, data presentation, and conclusion drawing. The research results show that the game-based approach, particularly through the Word Warriors game, significantly enhances student engagement, critical thinking skills, understanding of literacy concepts, and enriches their Indonesian vocabulary. This approach not only improves students' proficiency in the Indonesian language but also helps make the learning process more relevant and engaging for them. These findings imply that the game-based learning approach can be more widely applied as an effective strategy in enhancing students' literacy and learning motivation.